SAT-242 Isolated Adrenocorticotropic Hormone Deficiency Secondary to the PD-1 Inhibitor Pembrolizumab - Mathew, Justin (J Endocr Soc, 2020)
Background: Immune checkpoint inhibitors (ICI’s) are now indicated in the treatment of several solid tumors and have improved the prognosis of patients with advanced malignancy. The expanded use of ICI’s has led to the rise of otherwise rare autoimmune sequelae. The overall incidence of ICI-induced autoimmune hypophysitis has increased to approximately 10%, but is only estimated to be 0.4% with PD-1 inhibitors specifically (1). Isolated ACTH deficiency from immune checkpoint inhibitors is rare, and very few cases secondary to the PD-1 inhibitor pembrolizumab have thus far been reported. Clinical Case: A 75-year old woman with history of Stage IV lung adenocarcinoma presented to oncology clinic in July 2019 with progressive weakness, weight loss, and confusion for several weeks. She was found to be hypotensive and dehydrated in the clinic and subsequently was admitted to the hospital. A comprehensive infectious work-up was non-contributory. History revealed that after treatment failure with carboplatin, she was treated with pembrolizumab from January 2017 to June 2019 with excellent response. Laboratory evaluation on admission demonstrated an undetectable AM cortisol level of < 1 ug/dL (n 5-25 ug/dL) with concomitant ACTH < 5pg/mL (Roche cobas, n 7.2-63 pg/mL), consistent with central adrenal insufficiency. Testing of the remainder of the pituitary axis, including TSH (0.83uU/mL, n 0.4-4.6 uU/mL), FSH (34.7 mIU/mL, n <150mIU/mL), LH (12.6mIU/mL, n <60 mIU/mL), and IGF-1 (33ng/mL, n 34-245ng/mL), all returned within normal limits. Further chart review verified that she had not been exposed to any form of glucocorticoids within the past 6 months. MRI brain with contrast demonstrated no obvious pituitary disease. The patient was started on 5mg of prednisone daily, with significant improvement in mental status, appetite, and blood pressure. She was discharged home on maintenance prednisone for adrenal insufficiency due to presumed isolated corticotroph destruction. Conclusions: Isolated ACTH deficiency is a very rare but potential consequence of pembrolizumab use. It can be especially difficult to diagnose in patients on chemotherapy who are at higher risk for dehydration and failure to thrive. Duration of pembrolizumab therapy should not preclude the diagnosis of isolated ACTH deficiency, as it can occur even as late as 2.5 years into therapy. Reference: (1) Chang, L., Barroso-Sousa, R., Tolaney S., Hodi F.S., Kaiser, U.B., Min, L. Endocrine Toxicity of Cancer Immunotherapy Targeting Immune Checkpoints, Endocr Rev. 2019;40;17–65.